(3efGUjH GdTWQfLs - (3eMeO Hf jMji Hf YHO Gddg, CHh HcQ GdUhdj, hbO jYQa HGdTWQfLj,J (B335 (3g` s ((3CMeO Hf eHGQcTGg GdeUQi GdMfai s)
(3ChdgG (B:s
(3HYO GdHSedI (B:(3gPG cJGH GdafGg ai efUhHGJ GdTWQfL GdZdhHGJ GdJi JLQi Hjf MPGbgG HMSf GSJNQGLgG hZehVgG Yf ef JfbU WHbI ajgG s
(3BNQgG (B:s
(3JeJ GdefUhHI hgj BNQ GdefUhHGJ GdJi hLOJgG ai fSNI GdUhdi HNWg YfO CHj HcQ GdefjLiGfJgi s
(3fbdG Yf fSNI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa (B- (3U (B164 s
Keywords: (3GdTWQfLs